Robustness in an Ultrasensitive Motor - Guangzhe Liu (American Society for Microbiology, 2020)
ABSTRACT In Escherichia coli, the chemotaxis response regulator CheY-P binds to FliM, a component of the switch complex at the base of the bacterial flagellar motor, to modulate the direction of motor rotation. The bacterial flagellar motor is ultrasensitive to the concentration of unbound CheY-P in the cytoplasm. CheY-P binds to FliM molecules both in the cytoplasm and on the motor. As the concentration of FliM unavoidably varies from cell to cell, leading to a variation of unbound CheY-P concentration in the cytoplasm, this raises the question whether the flagellar motor is robust against this variation, that is, whether the rotational bias of the motor is more or less constant as the concentration of FliM varies. Here, we showed that the motor is robust against variations of the concentration of FliM. We identified adaptive remodeling of the motor as the mechanism for this robustness. As the level of FliM molecules changes, resulting in different amounts of the unbound CheY-P molecules, the motor adaptively changes the composition of its switch complex to compensate for this effect. IMPORTANCE The bacterial flagellar motor is an ultrasensitive motor. Its output, the probability of the motor turning clockwise, depends sensitively on the occupancy of the protein FliM (a component on the switch complex of the motor) by the input CheY-P molecules. With a limited cellular pool of CheY-P molecules, cell-to-cell variation of the FliM level would lead to large unwanted variation of the motor output if not compensated. Here, we showed that the motor output is robust against the variation of FliM level and identified the adaptive remodeling of the motor switch complex as the mechanism for this robustness.